Various zebrafish models of Parkinson’s disease: what gives us hope - Soliman Wadan, Al-Hassan; Mohamed, Wael Mohamed Yousef (Elsevier, 2025)
The selection of appropriate animal models to study neurodegenerative and neurodevelopmental disorders, including Parkinson’s disease (PD), Alzheimer’s disease (AD), Huntington’s disease, schizophrenia, and epilepsy, depends on various criteria and limitations (Pienaar et al., 2010). An ideal animal model of PD should demonstrate histopathological characteristics such as progressive loss of dopaminergic neurons and nondopaminergic neurons, with symptoms appearing in adulthood (Barnhill et al., 2020). These models should also mimic clinical manifestations of PD, including motor features responsive to L-DOPA therapy, like bradykinesia, rigidity, postural instability, and resting tremor (Breger & Fuzzati Armentero, 2019; Pienaar et al., 2010). Rodent and primate models have been developed to explore disease mechanisms and enhance therapeutic outcomes using neurotoxic substances or genetic manipulation. Various toxins, such as 6-hydroxydopamine (6-OHDA), rotenone, paraquat, and 1-methyl-4-phenyl-1,2,3,6-tetra-hydropyridine (MPTP), have been used to selectively destroy nigrostriatal DA neurons, resulting in PD-like symptoms in animals (Burns et al., 1983; McKinley et al., 2005). Rotenone models are preferred for assessing neuroprotection due to their independent mechanism of neurotoxicity from the DA uptake transporter (DAT) (Pienaar et al., 2009; Tapias et al., 2010). Though these models offer valuable insights, they do not fully replicate all human PD symptoms. Transgenic approaches involving gene manipulation, such as overexpression, knock-out, knock-in, and knock-down of PD genes, have been used to study PD (Sfar et al., 2009; Xiong et al., 2009). However, high-throughput screenings for genetic interactions or pharmacological therapies can be costly and time-consuming when using murine or nonhuman primate models (Faust et al., 2009). As alternatives, models involving zebrafish (ZF), fruit flies, nematodes, and anurans have gained attraction due to their efficiency and contribution to understanding disease mechanisms and novel therapeutic strategies (Pienaar et al., 2010).